Optimum condition investigation on precipitating of calcium carbonate from natural limestone from Bayan soum (Mongolian Journal of Agricultural Sciences, 2021)
Calcium carbonate (CaCO3) is the most widely used filler material in paper, paint, plastic, food, ceramic, cosmetic, medicine and other industries. In the present paper, precipitated calcium carbonate (PCC) has been produced from natural limestone powder (NLP) by the Calcination-Dissolution-Precipitation (CDP) method. Calcination, dissolution and precipitation experiments were carried out under various conditions including: calcination temperature (800, 850, 900, 950, 1000 and 1050 °C), dissolution time (5, 10, 15, 20 and 25 min) and precipitation time (10, 20, 30, 40, 50 and 60 sec). The analyses by XRF showed that the natural limestone contains 80.97% CaCO3 (47.39% CaO), produced PCC sample contains 94.47% CaCO3 (55.81% CaO). It can be seen that the produced PCC sample more purified than natural limestone.Баянгийн ордны шохойн чулуунаас кальцийн карбонат тунадасжуулах тохиромжтой нөхцөлийн судалгааКальцийн карбонатыг цаас, будаг, хуванцар, хүнс, керамик, косметик, эмийн болон бусад үйлдвэрлэлд маш өргөн ашигладаг. Бид энэхүү судалгаагаар байгалийн шохойн чулуунаас тунадасжуулсан кальцийн карбонатийг гарган авахдаа Calcination-Dissolution-Precipitation (CDP) буюу шатаан-уусгаж-тунадасжуулах  аргыг ашигласан. Байгалийн шохойн чулууг шатаах туршилтыг 800, 850, 900, 950, 1000 болон 1050°C хэмд, уусгалтын хугацаа 5, 10, 15, 20 болон 25 минут, тунадасжуулах хугацааг 10, 20, 30, 40, 50 болон 60 секунд гэсэн  хувилбаруудтай явуулсан. Рентген флюресценцийн шинжилгээгээр байгалийн шохойн чулууны дээжинд 80.97% CaCO3, тунадасжуулсан шохойн чулууны дээжинд 94.47% CaCO3 агуулагдаж байгаа нь тогтоогдсоноос үзвэл шатаан-уусгаж-тунадасжуулах аргаар илүү цэвэршилттэй кальцийн карбонат гарган авах боломжтойг харуулж байна. Түлхүүр үг:  Шатаах, уусгах, тунадасжуулах, CaCO3, Ca(OH)2